(untitled) (Indian Journal of Arid Horticulture, 2017)
A study was conducted to assess the impact of water stress on physiological activities and metabolite constitution in musk melon and snap melon. The field grown plants were subjected to water stress for 5 and 10 days when the plants were 45 days old. Subsequently, the stressed plants were re-irrigated and allowed to recover up to 15 days after re-irrigation. The data on photosynthetic rate and associated parameters and secondary metabolites such as total sugar, phenols, alkaloids, tannins and flavonoid content were assessed at every stage. The data revealed that snap melon the photosynthetic rate recovered fast and nearly reached to the values in control plants, however in musk melon the recovery was low. The data on flavonoid constitution of snap melon reveals that the magnitude of this metabolite increases with imposition of stress as well as age of plants showing thereby that the plants have potential to scavenge the ROS moieties developed due to water stress.